2018
DOI: 10.1021/acs.jmedchem.8b00670
|View full text |Cite
|
Sign up to set email alerts
|

4-Substituted Benzenesulfonamides Incorporating Bi/Tricyclic Moieties Act as Potent and Isoform-Selective Carbonic Anhydrase II/IX Inhibitors

Abstract: As a part of our efforts to expand chemical diversity in the carbonic anhydrases inhibitors (CAIs), three small series of polyheterocyclic compounds (4-6) featuring the primary benzenesulfonamide moiety linked to bi/tricyclic scaffolds were investigated. Highly effective inhibitors against the target tumor-associated hCA IX (low nanomolar/subnanomolar potency levels) showing significant functional selectivity profile toward hCA I, II, and IV isozymes were identified. Molecular docking studies clarified the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…To clarify the reasons for the activities displayed by the newly designed compounds, molecular docking studies were attained. Docking calculations were performed using a protocol already successfully applied in our previous work on CA inhibitors 39 . Namely, AutoDock4.2 (AD4) 30 , 37 was employed together with the AutoDock4(Zn) forcefield 31 , which was specifically designed to accurately predict the binding interactions of ligands docking to zinc metalloproteins.…”
Section: Resultsmentioning
confidence: 99%
“…To clarify the reasons for the activities displayed by the newly designed compounds, molecular docking studies were attained. Docking calculations were performed using a protocol already successfully applied in our previous work on CA inhibitors 39 . Namely, AutoDock4.2 (AD4) 30 , 37 was employed together with the AutoDock4(Zn) forcefield 31 , which was specifically designed to accurately predict the binding interactions of ligands docking to zinc metalloproteins.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the established role of CA IX/CA XII in cancer, many classes of potent and selective CA IX/CA XII inhibitors have been developed which have shown promising activity in in vitro as well as in vivo models. Many researchers have put their effort to develop potent CA IX/CA XII inhibitors, which selectively inhibit CA IX/CA XII or both over the cytosolic CA isoforms 269–316 …”
Section: Drug Design and Development Strategies For Selective Caismentioning
confidence: 99%
“…It was >1370‐, 577‐, and 990‐fold selective for hCA IX over hCA I, hCA II, and hCA IV. The molecular docking study indicated that pyrimidine ring nitrogen of compound 304 actively participated to establish H‐bond interaction with Q71 and Q92 side chains, which may be provided favorable binding with hCA IX led to achieving high affinity for hCA IX 311 . Bozdag et al developed 2‐aminophenol‐4‐sulfonamide and its urea analogues by modifying lead molecule SLC‐0111as potent hCA IX/hCA XII inhibitors.…”
Section: Drug Design and Development Strategies For Selective Caismentioning
confidence: 99%
See 1 more Smart Citation
“…Each inhibitor was tested in triplicate, in serial dilutions starting from 0.01 to 0.1 mM. An incubation time of 15 min between inhibitor and enzyme has been used, as reported earlier, in order to be sure that the enzyme-inhibitor complex has been formed [2,25,27,[39][40][41][42][43][44][45][46][47][48][49][50]. The inhibition constants were obtained by using the Cheng-Prusoff equation [39,[51][52][53] and are the mean from three determinations.…”
Section: Ca Inhibitionmentioning
confidence: 99%